Improved machine for weeding fields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A new twist on an age-old approach spells trouble for weeds in lowland rice fields. IRRI researchers have now combined the basic uprooting and burying action of a traditional, pronged lowland paddy-puddlerwith a completely reconfigured design...